MORPHOFUNCTIONAL CHANGES IN THE MAXILLARY SINUSES UNDER THE INFLUENCE OF PESTICIDES (International journal of artificial intelligence, 2024)
This study investigates the morphofunctional changes in the structure of the maxillary sinuses under the influence of pesticides. Pesticides are known to exert toxic effects on the body, particularly damaging the respiratory tract and sinus functions. The study utilized a laboratory animal model to analyze the impact of pesticides on the maxillary sinuses. In recent years, concerns about environmental degradation and the widespread use of chemical substances such as pesticides have raised alarms about their potential negative effects on sinus functions.